Hallucinations at the interface of philosophy and the empirical sciences - Dolcini, Nevia (Frontiers in Psychology, 2025)
Hallucinations sit at the crossroads of philosophy and the empirical sciences, but are often approached with divergent aims. In philosophy, they are mainly treated stipulatively as experiences subjectively indistinguishable from veridical perception and used to probe theories of perception, justification, and consciousness. Empirical research, by contrast, investigates heterogeneous, clinically embedded hallucinatory phenomena, many of which differ phenomenologically from ordinary perception. This paper diagnoses the conceptual misalignment that follows from this divergence and offers a preliminary framework to narrow it through conceptual analysis. Rather than advancing a single unifying theory, I clarify key distinctions, including indistinguishability, insight, sense of reality, agency, and ownership, and sketch points of contact with constructs in the sciences. First, I examine leading empirical models—bottom-up, top-down, and predictive processing—highlighting what each explains and where each is limited. Second, I re-situate hallucinations within core philosophical debates on perception, mental imagery, and phenomenology, showing how empirical findings both inform and complicate current accounts. Third, I assess interdisciplinary developments that challenge unitary models and support pluralist, integrative approaches. Hallucinations are thus recast as a family of related phenomena, and the analysis provides theoretical coordinates for more productive interaction between philosophy and science.